O. F. Robinson, T. D. Ferguson, W. M. Gordon, An Introduction to European Legal History, 1985 - Adam Czarnota (Czasopismo Prawno-Historyczne, 1989)
Recenzja: O. F. Robinson, T. D. Ferguson, W. M. Gordon, An Introduction to European Legal History, Professional Books: Abingdon 1985